Back to School - Sustaining Recurring Child-Robot Educational Interactions After a Long Break - Ligthart, Mike E. U.; de Droog, Simone M.; Bossema, Marianne; Elloumi, Lamia; de Haas, Mirjam; Smakman, Matthijs H. J.; Hindriks, Koen V.; Allouch, Somaya Ben (2024 19th ACM/IEEE International Conference on Human-Robot Interaction (HRI), 2024)
Maintaining the child-robot relationship after a significant break, such as a holiday, is an important step for developing sustainable social robots for education. We ran a four-session user study (n = 113 children) that included a nine-month break between the third and fourth session. During the study, participants practiced math with the help of a social robot math tutor. We found that social personalization is an effective strategy to better sustain the child-robot relationship than the absence of social personalization. To become reacquainted after the long break, the robot summarizes a few pieces of information it had stored about the child. This gives children a feeling of being remembered, which is a key contributor to the effectiveness of social personalization. Enabling the robot to refer to information previously shared by the child is another key contributor to social personalization. Conditional for its effectiveness, however, is that children notice these memory references. Finally, although we found that children's interest in the tutoring content is related to relationship formation, personalizing the topics did not lead to more interest in the content. It seems likely that not all of the memory information that was used to personalize the content was up-to-date or socially relevant.CCS CONCEPTS* Applied computing → Education; * Human-centered computing → Empirical studies in interaction design; * Computing methodologies → Cognitive robotics.